Half-Wave Potentials and In Vitro Cytotoxic Evaluation of 3-Acylated 2,5-Bis(phenylamino)-1,4-benzoquinones on Cancer Cells - Benites, Julio (Molecules, 2019)
A broad range of 3-acyl-2,5-bis(phenylamino)-1,4-benzoquinones were synthesized and their voltammetric values, as well as in vitro cancer cell cytotoxicities, were assessed. The members of this series were prepared from acylbenzoquinones and phenylamines, in moderate to good yields (47–74%), through a procedure involving a sequence of two in situ regioselective oxidative amination reactions. The cyclic voltammograms of the aminoquinones exhibit two one-electron reduction waves to the corresponding radical-anion and dianion, and two quasi-reversible oxidation peaks. The first and second half-wave potential values (E(1/2)) of the members of the series were sensitive to the push-pull electronic effects of the substituents around the benzoquinone nucleus. The in vitro cytotoxic activities of the 3-acyl-2,5-bis(phenylamino)-1,4-benzoquinones against human cancer cells (bladder and prostate) and non-tumor human embryonic kidney cells were measured using the MTT colorimetric method. The substitution of both aniline groups, by either methoxy (electron donating effect) or fluorine (electron withdrawal effect), decreased the cytotoxicity in the aminoquinones. Among the members of the unsubstituted phenylamino series, two of the 18 compounds showed interesting anti-cancer activities. A preliminary assay, looking for changes in the expression of selected genes, was performed. In this context, the two compounds increased TNF gene expression, suggesting an association with an inflammatory-like response.